Analysis of West Java Export Leading Product Competitiveness - Nurfitriya, Mira (The International Journal of Business Review (The Jobs Review), 2021)
This study aims to determine the analysis of the competitiveness of export products in West Java for the 2015-2019 period. The analysis used in this research is comparative advantage index analysis using Revealed Symmetric Comparative Advantage (RSCA). By using the comparative advantage index analysis per commodity in West Java, the results show that most of the superior products in West Java have not experienced significant changes, but there will be some products that have decreased competitiveness (comparative). The low competitiveness of superior products in West Java is caused by several things, such as the non-conducive macro economy, weak technology development, weak competitive climate (micro); and the inaccuracy of the business development strategy implemented by business actors and other shareholders. In addition to these things, there are several inhibiting factors in increasing the competitiveness of West Java's leading export products, among others, unsettled production factors, poor institutional factors, and the relationship and utilization of supporting industries that have not been maximized.Â